Structural monitoring and modeling of the mechanical deformation of three-dimensional printed poly(ε-caprolactone) scaffolds - Ribeiro, João F. M. (2017)
Three-dimensional (3D) printed poly(ε-caprolactone) (PCL) based scaffolds have being proposed for different tissue engineering applications. This study addresses the design and fabrication of 3D PCL constructs with different struts alignments at 90°, 45° and 90° with offset. The morphology and the mechanical behavior under uniaxial compressive load were assessed at different strain percentages. The combination of a new compressionCT device and micro computed tomography (micro-CT) allowed understanding the influence of pore geometry under controlled compressive strain in the mechanical and structural behavior of PCL constructs. Finite element analysis (FEA) was applied using the micro-CT data to modulate the mechanical response and compare with the conventional uniaxial compression tests. Scanning electron microscopic analysis showed a very high level of reproducibility and a low error comparing with the theoretical values, confirming that the alignment and the dimensional features of the printed struts are reliable. The mechanical tests showed that the 90° architecture presented the highest stiffness. With the compressionCT device was observed that the 90° and 90° with offset architectures presented similar values of porosity at same strain and similar pore size, contrary to the 45° architecture. Thus, pore geometric configurations affected significantly the deformability of the all PCL scaffolds under compression. The prediction of the FEA showed a good agreement to the conventional mechanical tests revealing the areas more affected under compression load. The methodology proposed in this study using 3D printed scaffolds with compressionCT device and FEA is a framework that offers great potential in understanding the mechanical and structural behavior of soft systems for different applications, including for the biomedical engineering field.